Development of a pipeline for exploratory metabolic profiling of infant urine - Jackson,FL; Georgakopoulou,N; Kaluarachchi,M; Kyriakides,M; Andreas,N; Przysiezna,N; Hyde,M; Modi,N; Nicholson,J; Wijeyesekera,A; Holmes,E (Journal of Proteome Research, 2016)
Numerous metabolic profiling pipelines have been developed to characterize the composition ofhuman biofluids and tissues, the vast majority of these being for studies in adults. To accommodatelimited sample volume and to take into account the compositional differences between adult andinfant biofluids, we developed and optimized sample handling and analytical procedures for studyingurine from newborns. A robust pipeline for metabolic profiling using NMR spectroscopy wasestablished, encompassing sample collection, preparation, spectroscopic measurement andcomputational analysis. Longitudinal samples were collected from five infants from birth until 14months of age. Methods of extraction, effects of freezing and sample dilution were assessed andurinary contaminants from breakdown of polymers in a range of diapers and cotton wool balls wereidentified and compared, including propylene glycol, acrylic acid and tert-butanol. Finally,assessment of urinary profiles obtained over the first few weeks of life revealed a dramatic change in composition, with concentrations of phenols, amino acids and betaine altering systematically overthe first few months of life. Therefore, neonatal samples require more stringent standardization ofexperimental design, sample handling and analysis compared to adult samples in order toaccommodate the variability and limited sample volume.